Conventional Neoclassical Test Of Economic And Technical Efficiencies In Pearl Millet Production In Niger State, Nigeria - Mohammed Sanusi, Sadiq, (International Journal of Scientific Research and Management (IJSRM), 2015)
This study determines the resource use efficiency in pearl millet production in Niger State, Nigeria. Multistage sampling technique was employed to elicit information from 160 millet framers throughadministration of pre-tested questionnaire. Data collection was for 2014 cropping season. Productionfunction analyses which incorporate the conventional neoclassical test of economic and technicalefficiencies were used as the analytical technique. Findings revealed that the farmers were inefficient in theuse of all the resources. Generally, inputs such as farm size, family labour, hired labour, seeds andfertilizers were under-utilized, while herbicides were over-utilized. The results indicate that there is need tomake inputs such as fertilizer, improved seeds and herbicides affordable and accessible to the farmers so asto improve efficiency.